2019
DOI: 10.1021/acs.langmuir.9b02604
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Influences of Solvent Boiling Point and Alkyl Chains on the Adlayer Crystallinity of Furan-Diketopyrrolopyrrole-Thienylene Copolymer at Molecular Level

Abstract: Crystallinity of the polymer poly­(3,6-difuran-2-yl-2,5-di­(2-octyldodecyl)-pyrrolo­[3,4-c]­pyrrole-1,4-dione-altthieylenevinylene) (PDVF) adlayers casted from low-boiling-point (L-bp), medium-bp (M-bp), and high-bp (H-bp) solvents was investigated through scanning tunneling microscopy (STM) and analyzed by the assistance of Hansen solubility parameter (HSP) theory and molecular dynamics (MD) simulations. Crystallinity of the PDVF adlayers increases evidently from the L- to H-bp solvents. Also, the solvent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It is well known in STM studies that alkyl chains are usually imaged as lowestcontrast trenches because of their much lower electron density in comparison to that of aromatic backbones. [21][22][23][24][25] The alkyl chains in the trenches can be recognized in the high-resolution image in Fig. 3b (indicted by an arrow).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known in STM studies that alkyl chains are usually imaged as lowestcontrast trenches because of their much lower electron density in comparison to that of aromatic backbones. [21][22][23][24][25] The alkyl chains in the trenches can be recognized in the high-resolution image in Fig. 3b (indicted by an arrow).…”
Section: Resultsmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) has unique advantages in investigating surface structures and processes at a molecular level. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Meanwhile, theoretical research based on density functional theory (DFT) provides a deep understanding of the interaction mechanisms, structural transformations, optoelectronic properties and functions of organic-organic and organicsubstrate systems. 25,[30][31][32][33] By combining these two powerful tools, the silver substrate is suggested to be able to reduce the energy barrier of bowl-to-bowl inversion of aromatic compounds as well.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the sensitivity of the CAS signal to the local molecular ordering of charge-occupied regions, we fabricated highordering and low-ordering pBTTT films, respectively. Since employing a high boiling point solvent and thermal annealing have been shown to improve crystallinity and structural ordering of polymeric films, [25,26] the highly ordered pBTTT film was obtained by using 1,2-dichlorobenzene as the solvent followed by thermal annealing, while the low-ordering sample was spun from a chloroform solution without annealing (see the Experimental Section for details). Note that the experimental results presented in the other parts of this work were obtained with the high-ordering pBTTT film unless specified.…”
Section: Molecular Ordering Probed With Casmentioning
confidence: 99%
“…15 These solvents possess diverse characteristics including solubility, toxicity, boiling point, viscosity, and polarity. 16,17 Newbloom et al investigated the gelation of poly(3-alkylthiophene)s (P3ATs) in a mixture of good and poor solvents. 18 They found that for P3HT in dichlorobenzene, more poor-solvent n-dodecane results in smaller, abundant fiber formation and better electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%